Cognitive Deception: Cognitive Hacking Phenomenon and Cognitive Security - Luomala, Mikko; Naarmala, Jyri (Academic conferences international, 2026)
Cybercriminality is an actively discussed topic in in criminology. While technical cybersecurity has evolved, increasing number of different types of technical solutions have been created to defend against cyberattacks. In security and cybersecurity, the weakest link is often considered to be a human. It seems that while malware attacks are increasing in numbers, also social engineering or cognitive hacking has increased. This paper explores the use and definition of a concept of cognitive deception in previous studies. Used dataset for this study was taken from SCOPUS database and qualitative meta-analysis (QMA) was used for analysing the content of the documents. The QMA method was selected for its suitability in content analysis of scientific-, as well as potential grey literature. Evolving technology has created new approaches for manipulating people. The analysis of research data indicates that cognitive hacking relates to definitions of cybercrime, cyberattack, warfare, and hybrid threats. This study contributes to the discussion about cognitive security.
Keywords: Cybercrime; Criminology; Cognitive Deception; Cognitive Hacking; Cyberattack; QMA; Qualitative Meta-Analysis; fi=Tietojärjestelmätiede|en=Information Systems Science|; fi=Tuotantotalous tekn|en=Industrial Management tech|